The Effect of High Flow Nasal Cannula (HFNC) on the Use of Ventilators in Severe to Critical COVID-19 Patients - Firdausintika, Lavely Rakhmatan; Syafa’ah, Irmi; Airlangga, Prananda Surya; Kriswidyatomo, Prihatma; Setiawan, Herley Windo; Marhana, Isnin Anang (Coronaviruses, 2026)
BackgroundSince the Coronavirus Disease 2019 (COVID-19) outbreak, clinicians have been seeking alternative therapies to improve patient conditions due to limited ventilator availability. The use of high-flow nasal cannula (HFNC) remains a debate regarding its potential to reduce intubation rates or worsen patient conditions.ObjectiveThe objective of this study was to analyze the effect of HFNC on ventilator usage in severe to critical COVID-19 patients.MethodsThis is an observational analytical study with a retrospective cohort design using medical record data of patients with severe to critical COVID-19 at Airlangga University Hospital from March, 2021 to August, 2021.ResultsOut of 137 data, no significant relationship was found between the use of HFNC and ventilator usage in severe to critical COVID-19 patients (p-value=0.337). The difference in oxygen therapy has a significant impact on patient survival rates and duration of patient care (p-value=<0.001).ConclusionThis study included 137 research samples: 69 males and 68 females, with an average age of 52.3 years, the majority presenting with diabetes and hypertension. Common symptoms included dyspnea, cough, and fever. Physical examination showed an average heart rate (HR) of 104 bpm, median respiratory rate (RR) of 30 breaths/minute, median blood oxygen level (SpO2) of 86%, average systolic blood pressure (SBP) of 138 mmHg, median diastolic blood pressure (DBP) of 80 mmHg, and median body temperature of 37.5°C. The median duration of patient care in this study was 8 days. No significant influence was reported between the use of HFNC and ventilator usage in severe to critical COVID-19 patients. A significant impact of HFNC administration on patient survival rates and duration of patient care was also reported.
Keywords: systolic blood pressure